2020
DOI: 10.1016/j.jallcom.2020.155505
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the high-pressure behavior of ZnV2O6, Zn2V2O7, and Zn3V2O8

Abstract: P09.-A high-pressure, low temperature, synchrotron single crystal x-ray diffraction study of the ordering of the confined water in microporous AlPO4-54•xH2O

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 50 publications
8
47
2
Order By: Relevance
“…As a consequence, their properties are being currently systematically studied. [1][2][3][4][5][6][7][8] In addition to technological applications, Zn 2 V 2 O 7 has recently raised attention because of its interesting behavior under high-pressure conditions. 8 In particular, it has been reported that Zn 2 V 2 O 7 (with a bulk modulus of 58 GPa (ref.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a consequence, their properties are being currently systematically studied. [1][2][3][4][5][6][7][8] In addition to technological applications, Zn 2 V 2 O 7 has recently raised attention because of its interesting behavior under high-pressure conditions. 8 In particular, it has been reported that Zn 2 V 2 O 7 (with a bulk modulus of 58 GPa (ref.…”
Section: Introductionmentioning
confidence: 99%
“…7)) is extremely more compressible that related vanadates like ZnV 2 O 6 and Zn 3 V 2 O 8 (with bulk moduli of 129 and 120 GPa, respectively). 7 Not only that, differences between the compressibility of Zn 2 V 2 O 7 and other vanadates also affect the structural stability under compression. According to X-ray diffraction experiments, Zn 2 V 2 O 7 experiences three structural phase transitions under relative small compression (pressure < 11 GPa), while in the other compounds there are no phase transitions in the same pressure range.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations